Simple in vitro assay of Arf GAPs and preparation of Arf proteins as substrates - Chen, Pei-Wen (Methods Cell Biol, 2015)
Defining the interaction of Arf GAPs with specific Arfs is important for understanding their functions in the endocytic system. Cell-based approaches have been valuable for identifying Arfs and Arf GAPs active in the endocytic compartment; however, the cell-based assays have some limitations in establishing relationships among the Arfs and ArfGAPs. Here we describe a simple in vitro assay that will provide a means for comparing Arfs as substrates and serve to complement cell-based studies.